2004
DOI: 10.1021/jf035012t
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of the Bcl-2/Bax Family Were Involved in the Chemopreventive Effects of Licorice Root (Glycyrrhiza uralensis Fisch) in MCF-7 Human Breast Cancer Cell

Abstract: Recently, cancer chemoprevention with strategies using foods and medicinal herbs has been regarded as one of the most visible fields for cancer control. Genistein in soy, American ginseng, and resveratrol are well-known to have antiproliferative properties in human breast cancer. Licorice root is a botanical, a shrub native to southern Europe and Asia, which primarily has desirable qualities in sweetening and herbal medicine. In this study, licorice (Glycyrrhiza uralensis Fisch) root also inhibits cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Licorice root contains alkaloids, polysaccharides, and flavonoids (32). Previous studies have reported licorice-induced cancer-specific cell death in various cancer cell types, including oral (7,11), prostate (13), colon (33) and breast cancer (34,35), through the inhibition of proliferation (11) and metastasis (18), cell-cycle arrest (13,14), and apoptotic cell death (14). Licochalcone-A, a chalconoid and a type of natural phenol, has been isolated from the root of the licorice plant and has exhibited various pharmacological effects, including antimalarial, anticancer, antibacterial and antiviral properties (7).…”
Section: Discussionmentioning
confidence: 99%
“…Licorice root contains alkaloids, polysaccharides, and flavonoids (32). Previous studies have reported licorice-induced cancer-specific cell death in various cancer cell types, including oral (7,11), prostate (13), colon (33) and breast cancer (34,35), through the inhibition of proliferation (11) and metastasis (18), cell-cycle arrest (13,14), and apoptotic cell death (14). Licochalcone-A, a chalconoid and a type of natural phenol, has been isolated from the root of the licorice plant and has exhibited various pharmacological effects, including antimalarial, anticancer, antibacterial and antiviral properties (7).…”
Section: Discussionmentioning
confidence: 99%
“…Preparations of plants, based on ancient recipes from Chinese or Japanese medical tradition, are mainly popular in Asia and North America [85]. Many mixtures are known to have an anticancerous effect in vitro [86][87][88], yet, no clinical trials have been performed to study efficacy and safety in breast cancer patients.…”
Section: Herbal Medical Productsmentioning
confidence: 99%
“…Presently, there is a considerable scientific discovery for the invention of anticancer agents from natural products [2]. In light of the continuing need for effective anticancer agents and edible plants are increasingly being considered as sources of anticancer drugs [3][4]. In extent, there is a large amount of scientific evidence showing that the fruits and vegetables lower the risk of cancer [5].…”
Section: Introductionmentioning
confidence: 99%